Absorptive Capacity: As a Mediator between Social Capital and Supply Chain Resilience in the Textile Industry of Thailanda - Safrida, Safrida; Suprayitno, Eddi; M.Ridha Tarigan, Nur; Ika Wardhani, Irine (International Journal of Supply Chain Management, 2020)
absorptive capacity (ABC) develops the effectives of external resource for the consistent comparative advantage which in turn helps in the enhancement of supply chain resilience (SCR). ABS is considered as a crucial factor of SCR as it permits the success of obtaining, integrating, altering, and manipulating the external information. The existence of ABC is essential for turning the collude relationships into positive ending. The purpose of present study is to re-explore the relationship between social capital (SCK) and SCR by incorporating the mediating role of ABC. For this purpose, the study collected the data from 193 employees of textile industry. Data are collected through questionnaire. Study applies structural equational modeling (SEM) approach for analyzing the empirical results. study used measurement model for testing the reliability and validity of the data. study applied structural model for testing proposed hypotheses. Finally, path analysis is conducted for testing the direct and indirect relationship among variables. Results of the study showed the positive relationship between SCK and SCR. Results further show that this positive relationship is significantly mediated by ABC. Results of the study suggests that the managers of the firm should subsidize the social capital of firm through absorptive capacity. Study further suggests that the managers of the firm can collaborate with other firms, it will enhance the SCK, which in turn effect SCR positively.